Construction of a hetero-epitaxial nanostructure at the interface of Li-rich cathode materials to boost their rate capability and cycling performances. Issue 48 (2nd December 2021) - Cao, Jun; Huang, Haijian; Qu, Yifan; Tang, Weijian; Yang, Zeheng; Zhang, Weixin
Abstract : A facile coating strategy is proposed to construct a hetero-epitaxial nanostructure at the interface of Li-rich cathode materials, and it effectively improves the rate capability and cycling performance of the cathode materials. Abstract : Lithium-rich cathode materials are considered to be promising candidate cathode materials for next-generation Li-ion batteries owing to their high specific capacities and low cost. Nevertheless, they still suffer from undesirable capacity loss and voltage decay during cycling. In this work, we propose a facile strategy to coat lithiated transition metal phosphates on the surface of Li-rich cathode materials. Strikingly, the coated material shows a hetero-epitaxial nanostructure at the interface between the coating layer and the cathode material. Such a coating layer with a unique interfacial structure could effectively boost the Li + solid-state diffusion kinetics, protect the cathode material from the corrosion of the electrolyte, and suppress the oxygen loss during the charge–discharge processes. Moreover, the lithiated phosphate coating layer can inhibit the formation of residual Li compounds upon long-term storage under an ambient atmosphere. Based on the above favorable properties, the lithiated phosphate coated Li-rich cathode material shows a high rate capability with a discharge capacity of 156 mA h g −1 obtained at 5 C and decent cyclic stability with a capacity retention of 93.4% achieved at 0.5 C after 140 cycles. This study investigates the interfacial engineering of Li-rich cathode materials via the construction of a Li + -conductive lithiated phosphate coating layer with a hetero-epitaxial interfacial nanostructure, which may offer an effective way to further improve the electrochemical performances of Li-rich cathode materials.